Some prosodic aspects in hindi - Srivastava, Chandrashekar Prasad (Journal of All India Institute of Speech and Hearing)
Intonation like everything else in language is one instrument in an orchestra. Some consider intonation as only a "peripheral part of communication", whereas according to some others intonation is ’central’ in communication.